Plant growth‐promoting rhizobacteria enhance wheat salt and drought stress tolerance by altering endogenous phytohormone levels and TaCTR1/TaDREB2 expression. Issue 4 (10th October 2017) - Barnawal, Deepti; Bharti, Nidhi; Pandey, Shiv S.; Pandey, Alok; Chanotiya, Chandan S.; Kalra, Alok
Abstract : Abiotic stresses such as salt and drought represent adverse environmental conditions that significantly damage plant growth and agricultural productivity. In this study, the mechanism of the plant growth‐promoting rhizo‐bacteria (PGPR)‐stimulated tolerance against abiotic stresses has been explored. Results suggest that PGPR strains, Arthrobacter protophormiae (SA3) and Dietzia natronolimnaea (STR1), can facilitate salt stress tolerance in wheat crop, while Bacillus subtilis (LDR2) can provide tolerance against drought stress in wheat. These PGPR strains enhance photosynthetic efficiency under salt and drought stress conditions. Moreover, all three PGPR strains increase indole‐3‐acetic acid (IAA) content of wheat under salt and drought stress conditions. The SA3 and LDR2 inoculations counteracted the increase of abscisic acid (ABA) and 1‐aminocyclopropane‐1‐carboxylate (ACC) under both salt and drought stress conditions, whereas STR1 had no significant impact on the ABA and ACC content. The impact of PGPR inoculations on these physiological parameters were further confirmed by gene expression analysis as we observed enhanced levels of the TaCTR1 gene in SA3‐, STR1‐ and LDR2‐ treated wheat seedlings as compared to uninoculated drought and salt stressed plants. PGPR inoculations enhanced expression of TaDREB2 gene encoding for a transcription factor, which has been shown to be important for improving the tolerance of plants to abiotic stress conditions. Our study suggest that PGPR confer abiotic stress tolerance in wheat by enhancing IAA content, reducing ABA/ACC content, modulating expression of a regulatory component (CTR1) of ethylene signaling pathway and DREB2 transcription factor.